Fully Floating Suspended Ceiling System: Experimental Evaluation of Structural Feasibility and Challenges. Issue 4 (November 2017) - Pourali, Atefeh; Dhakal, Rajesh P.; MacRae, Gregory; Tasligedik, Ali Sahin
Full scale shake table testing is conducted on a novel type of suspended ceiling called fully floating ceiling system, which is freely hung from the floor above lacking any lateral bracing and connections with the perimeters. A gap is provided on all sides of the ceiling. Throughout different tests, a satisfactory agreement between the fully floating ceiling response and simple pendulum theory was demonstrated. When subjected to input motions with significant energy in the floating ceiling's resonant frequency, the horizontal displacement of the ceiling exceeded the gap width resulting in pounding induced large acceleration pulses. To mitigate such effects, the perimeter gap fillers of a compressible material are proposed. The addition of perimeter isolation was found effective in inducing extra damping and protecting the ceiling from pounding impact; resulting in much reduced ceiling displacements and accelerations. Throughout the tests a single panel dislodgement was observed as the only instance of damage.